Mobile device security : a comprehensive guide to securing your information in a moving world - Fried, Stephen , 1962- (Taylor & Francis Group, 2010)
Explaining how mobile devices can create backdoor security threats, this title specifies immediate actions you can take to defend against these threats. Highlighting the risks inherent when mobilizing data, it supplies a proven methodology for identifying, analyzing, and evaluating these risks